Isolation of Mycosporine-like Amino Acids from Red Macroalgae and a Marine Lichen by High-Performance Countercurrent Chromatography: A Strategy to Obtain Biological UV-Filters. - Vega Sánchez, Julia; Bárcenas-Pérez, Daniela; Fuentes-Ríos, David; López-Romero, Juan Manuel; Hrouzek, Pavel; López-Figueroa, Félix; Cheel, José (MDPI, 2023)
Marine organisms have gained considerable biotechnological interest in recent years due to their wide variety of bioactive compounds with potential applications. Mycosporine-like amino acids (MAAs) are UV-absorbing secondary metabolites with antioxidant and photoprotective capacity, mainly found in organisms living under stress conditions (e.g., cyanobacteria, red algae, or lichens). In this work, five MAAs were isolated from two red macroalgae (Pyropia columbina and Gelidium corneum) and one marine lichen (Lichina pygmaea) by high-performance countercurrent chromatography (HPCCC). The selected biphasic solvent system consisted of ethanol, acetonitrile, saturated ammonium sulphate solution, and water (1:1:0.5:1; v:v:v:v). The HPCCC process for P. columbina and G. corneum consisted of eight separation cycles (1 g and 200 mg of extract per cycle, respectively), whereas three cycles were performed for of L. pygmaea (1.2 g extract per cycle). The separation process resulted in fractions enriched with palythine (2.3 mg), asterina-330 (3.3 mg), shinorine (14.8 mg), porphyra-334 (203.5 mg) and mycosporine-serinol (46.6 mg), which were subsequently desalted by using precipitation with methanol and permeation on a Sephadex G-10 column. Target molecules were identified by HPLC, MS, and NMR.
Keywords: Aminoácidos; Líquenes; Cromatografía; Algas marinas; Biotecnología marina; Countercurrent chromatography; Isolation; Marine lichen; Mycosporine-like amino acids; Photoprotection